DELAYED-TYPE HYPERSENSITIVITY RESPONSE IN AN ISOGENIC MURINE MODEL OF PARACOCCIDIOIDOMYCOSIS - Fazioli, R. D.; Singervermes, L. M.; Kashino, S. S.; Burger, E.; Defranco, M. F.; Moscardibacchi, M.; Calich, VLG (Kluwer Academic Publ, 1994)
The specific delayed-type hypersensitivity (DTH) response was evaluated in resistant (A/SN) and susceptible (B10.A) mice intraperitoneally infected with yeasts from a virulent (Pb18) or from a non-virulent (Pb265) Paracoccidioides brasiliensis isolates. Both strains of mice were footpad challenged with homologous antigens. Pb18 infected A/SN mice developed an evident and persistent DTH response late in the course of the disease (90th day on) whereas B10.A animals mounted a discrete and ephemeral DTH response at the 14th day post-infection. A/SN mice infected with Pb265 developed cellular immune responses whereas B10.A mice were almost always anergic. Histological analysis of the footpads of infected mice at 48 hours after challenge showed a mixed infiltrate consisting of predominantly mononuclear cells. Previous infection of resistant and susceptible mice with Pb18 did not alter their DTH responses against heterologous unrelated antigens (sheep red blood cells and dinitrofluorobenzene) indicating that the observed cellular anergy was antigen-specific. When fungal related antigens (candidin and histoplasmin) were tested in resistant mice, absence of cross-reactivity was noted. Thus, specific DTH responses against P. brasiliensis depend on both the host's genetically determined resistance and the virulence of the fungal isolate.
Keywords: CELLULAR IMMUNE RESPONSE; DELAYED-TYPE HYPERSENSITIVITY; ISOGENIC MURINE MODEL; P-BRASILIENSIS